EVALUASI DAN PENINGKATAN BELAJAR MATEMATIKA SMP DAERAH TERTINGGAL, TERDEPAN, DAN TERLUAR (3T): METODE SEDERHANA LOGIKA TAKTIS - Elim, Ph.D, Prof. Hendry Izaac (Universitas Pattimura, 2023)
This research presents an implementation result of mathematical knowledge for Junior High School level (SMP) through teaching assistant program particularly in remote area schools (3T area) of Maluku prefecture consisted of 1340 small islands which are rich of natural resources with a complicated growing system in education, economy and transportation due to the lack of technology. In this opportunity, Pattimura university sent the best group of scientists especially in the fields of mathematical logic, natural sciences, and English to treat Elementary and Junior High School students. The process of student’s education was carried out by detecting the students logic ability in calculating the mathematics complex summation tested through a step by step question and answer teaching’s transformation. The results show that in the beginning of study, all the 22 sample students of SMP Negeri 01, Namrole got 0% correct answer in a very simple summation question of (½+1/3 = ?). In the second tested question after the treatment of the solution teaching of the former one detected with 32% correct solution from the whole students. Next, by implementing the same teaching solution as the first and the second summation questions, we found 72.72% total correct answer for the whole 22 students. The 4th question was not conducted by students in the classroom because of the 1 hour school study had been over, and it would be homework for students. According to this work, the quality understanding of students is significantly dependent on the excellent knowledge of mathematics teacher